2002
DOI: 10.1007/s00455-002-0060-9
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Early Diet Textures as Indicators of Recovery from Dysphagia After Stroke

Abstract: We undertook this 12-month retrospective cohort study, of 186 teaching hospital inpatients, to determine how tolerance of differing diet textures after a stroke predicts recovery from dysphagia. Outcome measures were insertion of a percutaneous endoscopic gastrostomy (PEG) tube and/or ability to tolerate a normal diet 28 days after the stroke. Likelihood ratios for needing a PEG were highest for intolerance of pureed food. People who tolerated grade 1 fluids (300-600 cP) or thinner, or who tolerated a modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…A previous study encountered similar difficulty in predicting tube feeding dependency [18]. Among patients unable to tolerate grade 3 thickened fluids or a puree diet 14 days after their stroke, half recovered sufficiently to manage oral feeding [18]. According to BayesÕ theorem, this relatively low positive predictive value can be attributed to the low prevalence of tube feeding dependency in the study population [29].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A previous study encountered similar difficulty in predicting tube feeding dependency [18]. Among patients unable to tolerate grade 3 thickened fluids or a puree diet 14 days after their stroke, half recovered sufficiently to manage oral feeding [18]. According to BayesÕ theorem, this relatively low positive predictive value can be attributed to the low prevalence of tube feeding dependency in the study population [29].…”
Section: Discussionmentioning
confidence: 85%
“…Until further data demonstrate the utility of such an equation, clinicians should be more concerned with the presence or absence of the individual factors of the equation than the equation itself. A previous study encountered similar difficulty in predicting tube feeding dependency [18]. Among patients unable to tolerate grade 3 thickened fluids or a puree diet 14 days after their stroke, half recovered sufficiently to manage oral feeding [18].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A retrospective cohort study [32] showed that the ability to tolerate oral intake early after stroke is an indicator of improvement of dysphagia. Patients who tolerated thickened liquids and pureed foods 14 days post onset could be fed orally in the course of treatment with a 50% probability.…”
Section: Discussionmentioning
confidence: 99%
“…The article by Wilkinson et al in this issue [4], has made good preliminary headway in this direction. The authors conducted a retrospective study to determine the patient variables that lead clinicians to prescribe tube feedings, in particular percutaneous endoscopic gastrostomy (PEG).…”
mentioning
confidence: 99%